XXXth Congress of the International Society of Biomechanics, Jul 2-6 2012 in Melbourne, Australia (International Society of Biomechanics in Sports, 2012)
The 30th Conference of the International Society of Biomechanics in Sport will be held in Melbourne, Australia in July 2012. The conference will include an impressive line-up of keynote speakers, parallel scientific sessions, and applied sessions on gymnastics, football, golf and outdoor pursuits. Unique to this conference will be a Future Scientists Symposium and the inaugural Biomechanics Oscars. The half-day Future Scientists Symposium aims to enable local undergraduate students to participate in the conference, be inspired by the Young Blood Investigator, and meet the world leaders in Sports Biomechanics.